Tricyclic antidepressants inhibit homomeric Cys-loop receptors by acting at different conformational states - Gumilar, Fernanda Andrea (2008)
Tricyclic antidepressants not only inhibit monoamine reuptake but also modulate Cys-loop receptors. However, it is not understood how this modulation is involved in their therapeutic effects. We analyzed the mechanisms of inhibition of homomeric 5-HT(3A) and alpha7-5HT(3A) receptors by tricyclic antidepressants at the single-channel and macroscopic current levels. These drugs reduce agonist-evoked currents in a noncompetitive and concentration-dependent manner. When they act on the open state, the reduction is similar for both receptors and it is voltage-dependent, thus suggesting an open-channel block process in which the blocked channel can either close or remain stabilized. By acting on the resting state, tricyclic antidepressants reduce the peak current in a voltage-independent manner, with a potency 6-fold higher for 5-HT(3A) than for alpha7-5HT(3A) (IC(50): 6 microM and 1 microM for alpha7-5HT(3A) and 5-HT(3A), respectively). Thus, tricyclic antidepressants may act on closed channels at the unshared extracellular domain from where they inhibit channel opening. Single alpha7-5HT(3A) channels in the continued presence of tricyclic antidepressants show: i) reduced open durations, compatible with open-channel block; ii) reduced burst durations, compatible with closing of blocked channels; and iii) reduced frequency of opening events, compatible with both impaired opening and stabilization of a closed state. In summary, our study reveals that tricyclic antidepressants inhibit homomeric Cys-loop receptors by acting through different mechanisms at open and closed conformational states and probably at two different domains, namely, the pore in the open state and the extracellular domain in the closed state.